Utility of the Kimura technique for the definitive management of high jejunal atresia - Ampaipan Boonthai; Paul D. Losty (SpringerOpen, 2023)
Abstract Background Operative management of high jejunal atresia may be challenging due to significant size discrepancy between the dilated proximal jejunum and distal atretic bowel. Case presentation We report a female newborn infant with a high type 1 proximal jejunal atresia located precariously at the duodenojejunal flexure which was successfully corrected with the Kimura operation, i.e., jejunojejunostomy as originally first described for duodenal atresia. The patient was weaned onto full enteral feeds by the end of the first postoperative week and promptly discharged without complication(s). Conclusions The utility and versatility of Kimura's diamond-shaped anastomosis are highlighted in this unique case report.